Parameter Optimization Design and Experimental Validation of a Header for Electric Rice Reaper Binders Employed in Hilly Regions - Jinbo Ren; Difa Bao; Zhi Liang; Chongsheng Yan; Junbo Wu; Xinhui Wu; Shuhe Zheng (Agriculture)
The operation of electric rice reaper binders in hilly and mountainous areas currently faces the challenges of poor conveying efficiency and high harvest losses caused by the large dispersion of rice stem posture angles. In this study, we propose a multiparameter collaborative optimization method for improving header structure in an effort to address these challenges. First, key parameters influencing lifting performance and their operational ranges were determined based on a theoretical analysis of the stem-lifting mechanism’s kinematic characteristics. A dynamic model simulating the header’s lifting process was developed by using the ADAMS multibody dynamics platform. Subsequently, we designed a quadratic regression orthogonal rotation combination experiment with three factors, i.e., the stem-lifting speed ratio coefficient, the cutter installation position, and the header tilt angle, using the stem-lifting angle as the evaluation metric. The variance in the experimental data was analyzed with Design-Expert 13.0, and response surface methodology (RSM) was applied to elucidate the parameter interaction effects. The optimal parameter combination was identified as a speed ratio coefficient of 2.14, a cutter installation position of 258.79 mm, and a header tilt angle of 62.63°, yielding a theoretical stem-lifting angle of 2.36°. Field validation tests demonstrated an actual stem-lifting angle of 2.44° (relative error: 3.39%) and a header loss rate of 0.59%, representing a 49.6% reduction compared with the pre-optimized design. These results confirm that the optimized header satisfies operational requirements for hilly terrain rice harvesting, providing both theoretical guidance and technical advancements for the design of low-loss harvesting machinery.